Missing: Black Self-Representations in Canadian Educational Research - Henry, Annette (Canadian Journal of Education/Revue canadienne de l'éducation, 1993)
Black educational theory and practice have not been a priority in mainstream Canadian education. I discuss some epistemological issues underpinning alternative conceptualiza- tions of education of children of African descent. My starting point for the construction of such conceptualizations is the agency and subjectivity of Black women educators, a constant yet overlooked critical presence in the education of Black children. Having sketched some tensions and possibilities in African-centred and Black feminist discourses, I conclude that these standpoint epistemologies are useful tools to forge new and more relevant theory and practice, but that they must be re-shaped to the pedagogical realities of Black teachers and students in Canada. L’éducation des Noirs, dans ses aspects théorique ou pratique, n’est pas une priorité dans l’éducation canadienne. L’auteure discute de certaines questions épistémologiques qui sous-tendent des approches éducatives différentes pour les enfants de descendance afri- caine. Le premier élément servant à l’élaboration de ces approches est le rôle et la sub- jectivité des éducatrices de race noire, une présence constante et pourtant oubliée dans l’éducation des enfants noirs. Après un survol de certaines des tensions et possibilités dans les discours axés sur l’Afrique et les propos des féministes noires, l’auteure conclut que ces épistémologies sont des outils utiles pour forger de nouvelles théories et pratiques plus pertinentes, mais qu’elles doivent être repensées en fonction des réalités pédagogi- ques des enseignants et des élèves noirs au Canada.